Increasing the efficiency of diesel engines operation by changing the process of fuel injection into the combustion chamber - Ivanov Igor (E3S Web of Conferences, 2021)
This paper proposes the author’s method of developing a constructive solution for supplying fuel to the combustion chamber to reduce fuel consumption in operation on the basis of TIPS (theory of inventive problem solving).